Dia Sedap Sdn. Bhd. / Nurul Batrisyia Sofia Ahmad Sufi - Ahmad Sufi, Nurul Batrisyia Sofia (2020)
Dia Sedap Sdn. Bhd. offers frozen food products and services for customers, providing the variety of cake such mini pau, pau, doughnut and doughnut goreng sambal that gives high satisfaction of consumer. Our clients is customers identifying as high, middle and low class who want consume product with affordable price of product, simple product and healthy product. Dia Sedap Sdn. Bhd. is a company which focuses on production of our product in Malaysia. This company provided a unique product which is wanted by the customer nowadays as it is easy to consume and healthy. Our product look more interesting and unique with all a variety filling in our cake especially for those who like to try something new to eat. We also targeting busiest workers because we have delivery services of our product to customers home. Dia Sedap Sdn. Bhd. offers a variety of cakes that give nutrition of health, low sugar, low calories and receive halal certificates. Across Selangor, Johor and Perak particularly the Dia Sedap Sdn. Bhd. business has seen an explosion of growth over the year. Selangor is an area that many people get married especially Muslim Malay, it cause demand of cake is rise over the year.